What monetary policy framework in 2021? - Pierre Fortin (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2020)
This background paper was prepared for the Bank of Canada conference on the 2021 renewal of the inflation-control agreement between the Bank and the Government of Canada held online in August 2020. The first part of the paper focuses on the fact that the room for conventional monetary stimulus is being limited by the narrow space remaining between the neutral level of the policy interest rate, estimated to be 2.5 percent and expected to remain low for some time, and the effective lower bound on this policy rate, set by the Bank of Canada at 0.25 percent. Two means of getting greater monetary stimulus would be for the Bank to keep on purchasing long-term assets on a large scale, or to increase its inflation target by a couple of percentage points, say from 2 percent to 3 or 4 percent. But the macroeconomic effectiveness of the first option is uncertain, and there would most likely be strong political opposition to increasing the inflation rate to 4 percent, or even only to 3 percent. In the short term, therefore, federal and provincial budgets are the only policy instrument that can make up for the shortcomings of monetary policy - however difficult policy coordination may be - and bring the Canadian economy to fully recover from the current recession without delay. The second part of the paper reviews results that Bank of Canada researchers have obtained in comparing the macroeconomic performance of various monetary policy frameworks with the help of their macro-econometric model of the Canadian economy called ToTEM. I am led to conclude that the 2021 agreement should keep the current flexible inflation targeting framework and continue to have it operated independently by our central bank, but that a somewhat more flexible approach than in the past could be welfare-improving. In particular, it could specify that maximizing employment is a prime concern of the Bank of Canada jointly with keeping inflation low and stable. This dual concern has been the bread and butter of the US Federal Reserve since it was legislated by the Humphrey-Hawkins Act of 1978. It would be beneficial for Canadians if the renewed agreement began to clarify how the two instruments of monetary and fiscal policy will be coordinated to achieve these two interdependent macroeconomic goals of low inflation and maximum employment.
Keywords: 330; Geldpolitik; Trend; Prognose